2022
DOI: 10.3389/fpsyg.2022.745093
|View full text |Cite
|
Sign up to set email alerts
|

Family Income, Parental Education and Chinese Preschoolers’ Cognitive School Readiness: Authoritative Parenting and Parental Involvement as Chain Mediators

Abstract: This study examined the associations of family income and parental education with Chinese preschool children’s cognitive school readiness and the sequential mediating role of parenting style (i.e., authoritative parenting) and parental involvement in these relations. A total of 307 5–6 years old kindergarten children from Shanghai, China and their parents participated in the study. Using structural equation modeling method, the results indicated that parental education was directly related to children’s cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…These results highlight the differential impact of the two variables involved in SES, that is, parental educational level and household income. Our findings also reveal a difference, but, in the opposite direction, that is to say, in favor of parents’ education as was also found in the recent study conducted by Xia (2022). Using a direct model, this author showed that parental education is significantly related (.14) to the cognitive school readiness of children in kindergarten, whereas family income is not (.08).…”
Section: Discussionsupporting
confidence: 81%
“…These results highlight the differential impact of the two variables involved in SES, that is, parental educational level and household income. Our findings also reveal a difference, but, in the opposite direction, that is to say, in favor of parents’ education as was also found in the recent study conducted by Xia (2022). Using a direct model, this author showed that parental education is significantly related (.14) to the cognitive school readiness of children in kindergarten, whereas family income is not (.08).…”
Section: Discussionsupporting
confidence: 81%
“…This factor is an important consideration because one of the reasons mothers works is to earn a living to meet family needs. If the care costs incurred are too large, it will affect the household budget (Xia, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is the social environment, culture, and habits of the surrounding community. These factors include the market price of housemaid salaries, parenting habits, and the views of the surrounding community regarding child care (Handayani et al, 2019;Meier & Mead, 1978;Shao et al, 2022;Xia, 2022). Regarding ideal parenting, the opinion of working mothers in Indonesia is by several research results which state that child care depends on several factors, namely the condition of the child itself, the conditions and abilities of parents, socio-economic and socio-cultural environment in which the family lives (Amalia et al, 2022;Dey et al, 2021;Zimmermann et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on children and caregivers from low-income families found that parents who positively promote their children's learning at home, have contact with school and have few barriers to participating facilitate their children being more positive in communication with their peers or adults and more cooperative, self-controlled and prosocial in the family and school environment (Mcwayne et al, 2004b). Parental involvement positively predicts children's cognitive preparation, which includes children's language abilities (Xia, 2022).…”
Section: Conceptual Foundations and Hypothesis Developmentmentioning
confidence: 99%